1973
DOI: 10.1149/1.2403417
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Study of the Growth and Oxidation of Nickel Hydroxide Films

Abstract: The formation and oxidation of nickel hydroxide films under a variety of experimental conditions are studied using in situ ellipsometric measurements. Two forms of the hydroxide, which we assume to be the α and β forms reported by other workers, are found. The α‐ and β‐hydroxide layers are both transparent with real refractive indices of 1.52 and 1.46, respectively, at 6328Aå. Upon oxidation the two forms of hydroxide convert to different oxides, both of which absorb light. The process involved in the conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
59
2
1

Year Published

1973
1973
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 6 publications
9
59
2
1
Order By: Relevance
“…The oxidation of Ni(I1) oxide to NiOOH takes place via H+ transport through the oxide film [12]. Since this film is a poor conductor, the oxidation Cc: Visscher, E. Barendrecht / Anodic oxrde films of nickel Table 4 Refractive index (n -i k) for divalent nickel oxide and hydroxide species Species Medium Wavelength n This process is characterized by a current peak in the voltammogram.…”
Section: Oxidation Of Precycled Nickelmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of Ni(I1) oxide to NiOOH takes place via H+ transport through the oxide film [12]. Since this film is a poor conductor, the oxidation Cc: Visscher, E. Barendrecht / Anodic oxrde films of nickel Table 4 Refractive index (n -i k) for divalent nickel oxide and hydroxide species Species Medium Wavelength n This process is characterized by a current peak in the voltammogram.…”
Section: Oxidation Of Precycled Nickelmentioning
confidence: 99%
“…On the basis of the refractive indices of film Ni(OH), electrodes, Hopper and Ord [12] assume that the reduced form of oxidized nickel is P-Ni(OH),.…”
Section: Introductionmentioning
confidence: 99%
“…For a-Ni(OH)2 a value of 1.52 -0 i (X 632.8 nm) has been reported [3]. Density values of 3 Ni(OH)2.2 H20 (= a-Ni(OH)2) and~-Ni(OH)2 differ considerably: 2.6-2.8 g.cm-3 for a-Ni(OH)2; 3.9 g.cm-3 for~-Ni(OH)2 [I]; so it is concluded that the thin~-films as deposited here.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, Abd El Aal [8,9] confirmed that the film formed in the passive region is composed of NiO (inner) and b-Ni(OH) 2 (outer) in borate solutions; NiO being the passivating species. At potentials above a critical value, the b-Ni(OH) 2 film is converted to an Ni(III) oxide phase, identified by ellipsometry as b-NiOOH [10]. The conversion of b-Ni(OH) 2 to b-NiOOH is a complex process [10,11].…”
Section: Introductionmentioning
confidence: 99%